2015
DOI: 10.1016/j.tcb.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Independent Mechanisms of Notch Activity

Abstract: Interaction between the Notch receptor and Delta-Serrate-Lag2 (DSL) ligands is generally deemed to be the starting point of the Notch signaling cascade, after which, Notch is cleaved and the intracellular domain acts as a transcriptional co-activator. By contrast, Notch protein can become activated independent of ligand stimulus through recently identified endosomal trafficking routes as well as through aberrant regulation of Notch components during Notch trafficking, ubiquitination, and degradation. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 89 publications
1
46
2
Order By: Relevance
“…However, the role of Notch signaling in crystal cell growth and survival has been mainly investigated in the larval lymph gland [30, 31]. In agreement with these investigations, inhibiting the Notch pathway in circulating Lz + cells, either by down-regulating the expression of Suppressor of Hairless [Su(H)], the core transcription factor in the Notch pathway, or by overexpressing Suppressor of Deltex [Su(dx)], a negative regulator of Notch [45], resulted in a decrease in lz>GFP + cell number and impaired their growth, whereas the overactivation of Notch signaling consecutive to the expression of a constitutively active Su(H)-VP16 fusion protein [46], caused a strong increase in lz>GFP + cell number and size (S5 Fig). …”
Section: Resultsmentioning
confidence: 99%
“…However, the role of Notch signaling in crystal cell growth and survival has been mainly investigated in the larval lymph gland [30, 31]. In agreement with these investigations, inhibiting the Notch pathway in circulating Lz + cells, either by down-regulating the expression of Suppressor of Hairless [Su(H)], the core transcription factor in the Notch pathway, or by overexpressing Suppressor of Deltex [Su(dx)], a negative regulator of Notch [45], resulted in a decrease in lz>GFP + cell number and impaired their growth, whereas the overactivation of Notch signaling consecutive to the expression of a constitutively active Su(H)-VP16 fusion protein [46], caused a strong increase in lz>GFP + cell number and size (S5 Fig). …”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that Notch3 ECD accumulation in CADASIL occurs independently of ligand binding, suggesting that it may instead arise from a defect in Notch3 receptor trafficking. 28,29 In Drosophila , misregulation of endosomal trafficking of the Notch receptor had been linked to its aberrant activation 30 , a possibility that warrants investigation in CADASIL.…”
Section: Discussionmentioning
confidence: 99%
“…However, we could not confirm a transcriptional effect of Nef/NAKC via Notch1. A ligand-independent role of Notch1 is now recognized in endosomal trafficking (Palmer and Deng, 2015), shuttling surface proteins into endosomal compartments (Waters et al, 2012). Furthermore, the protein was found to be required for cytokine secretion in T cells (Benson et al, 2005, Manaster et al, 2010).…”
Section: Discussionmentioning
confidence: 99%